Bilio-pancreatic endoscopy during COVID-19 pandemic. (June 2020) - Bove, Vincenzo; Schepis, Tommaso; Boškoski, Ivo; Landi, Rosario; Orlandini, Beatrice; Pontecorvi, Valerio; Familiari, Pietro; Tringali, Andrea; Perri, Vincenzo; Costamagna, Guido
On 31 December 2019, the WHO China Country Office was informed of cases of pneumonia of unknown etiology detected in Wuhan (Hubei Province of China). In January 2020, a new coronavirus named SARS-CoV2 was isolated and, since that time, SARS-CoV2 related disease (COVID-19) rapidly spread all over the world becoming pandemic in March 2020. The COVID-19 outbreak dramatically affected the public-health and the health-care facilities organization. Bilio-pancreatic endoscopy is considered a high-risk procedure for cross-contamination and, even though it is not directly involved in COVID-19 diagnosis and management, its reorganization is crucial to guarantee high standards of care minimizing the risk of SARS-CoV2 transmission among patients and health-care providers. Bilio-pancreatic endoscopic procedures often require a short physical distance between the endoscopist and the patient for a long period of time, a frequent exchange of devices, the involvement of a large number of personnel, the use of complex endoscopes difficult to reprocess. On this basis, endoscopic units should take precautions with adjusted management of bilio-pancreatic endoscopy. The aim of this article is to discuss the approach to bilio-pancreatic endoscopy in the COVID-19 era with focus on diagnostic algorithms, indications, management of the endoscopic room, proper use of Personal Protective Equipment and correct reprocessing of instrumentation.